Analisis Efektivitas Pendekatan Matematika Realistik pada Pembelajaran Matematika Sekolah Dasar Kelas 4 - Unaenah, Een; Nabila, Aida; Qur’ani, Fathiya Cahaya (Lembaga Yasin AlSys, 2023)
Through an evaluation of 10 papers and one lesson plan for grade 4, this study aims to determine the effectiveness of learning mathematics using a realistic mathematics approach (PMR). This study combines a kind of literature study with a qualitative methodology. Data collection, including reading appropriate publications and lesson plans, can be carried out to determine the efficacy of a practical mathematics approach. The Realistic Mathematics Approach (PMR) is a great method for teaching and understanding mathematics which is very good for students. The focus of this approach is realistic concepts through relevant examples and questions and connecting them with real life which is expected for students to be able to master the material.